FRUCTOSE SYRUP OBTENTION FROM ENZYMATIC HYDROLYSED OF YAM STARCH (Dioscorea alata and Dioscorea rotundata) - SALCEDO M., Jairo G.; MONTES M., Everaldo J.; ZAPATA M., José E.; MÁRQUEZ H., Didier A.; DIAZ A., Miguel (Vitae, 2010)
This investigation evaluated the yield of fructose syrup production from extracted starch of two yam species ( Dioscorea alata , var. Diamond and Dioscorea rotundata , var. Espino). The experiment was conducted using an at random experimental design of multiple categorical factor analysis with two factors: a substrate concentration factor at five levels: 10, 20, 30, 40, 50% p/v and the yam species factor at two levels ( Dioscorea alata , var Diamond and Dioscorea rotundata , var Espino). To obtain fructose, initially glucose syrups were prepared by enzymatic hydrolysis of yam starch using the enzymes of Novozymes®,alpha-amylase Termamyl 120L (liquefaction stage) and AMG 300L (saccharification stage). At this stage, dextrose maximum equivalents (ED) obtained were 98.28 and 96.84 for a substrate concentration of 30%w/v. In a later stage isomerisation from glucose syrups to fructose syrups using the immobilized enzyme Sweetzyme of Novozymes® was carried out. The best results were achieved with substrate concentrations of 30% p/v for both yam species, which showed fructose concentrations of 220.57 and 210.36 g/L with conversions of 71.46% and 67.28% in Espino and Diamond yams respectively. No statistically significant differences were observed between the yam species ( D. alata var. Diamante and D. rotundata var. Espino) at a confidence level of 5%, regarding the production of fructose syrup.